2021
DOI: 10.1038/s41467-021-21693-4
|View full text |Cite
|
Sign up to set email alerts
|

General molten-salt route to three-dimensional porous transition metal nitrides as sensitive and stable Raman substrates

Abstract: Transition metal nitrides have been widely studied due to their high electrical conductivity and excellent chemical stability. However, their preparation traditionally requires harsh conditions because of the ultrahigh activation energy barrier they need to cross in nucleation. Herein, we report three-dimensional porous VN, MoN, WN, and TiN with high surface area and porosity that are prepared by a general and mild molten-salt route. Trace water is found to be a key factor for the formation of these porous tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Inspired by this idea, we consider molten salt (MS) synthesis, a classical method for preparing functional materials owing to its simplicity, speed, large-scale compatibility, and low cost. [24][25][26][27][28] The MS melts can exhibit homogeneous heat and mass transfer to carry out chemical transformation even at low temperature. [24,29] MS methods have been widely used in industrial production.…”
mentioning
confidence: 99%
“…Inspired by this idea, we consider molten salt (MS) synthesis, a classical method for preparing functional materials owing to its simplicity, speed, large-scale compatibility, and low cost. [24][25][26][27][28] The MS melts can exhibit homogeneous heat and mass transfer to carry out chemical transformation even at low temperature. [24,29] MS methods have been widely used in industrial production.…”
mentioning
confidence: 99%
“…
Figure 8. A) Synthesis scheme of crystalline mesoporous titanium oxynitride (Reproduced with permission from [ 178 ]) b) synthesis scheme of porous single MNs of vanadium, molybdenum, titanium, and tungsten via molten salt route, and c) their formation mechanism (Reproduced with permission from [ 180 ]).
…”
Section: Synthesis Of Porous Mnsmentioning
confidence: 99%
“…The molten salt route can be extended to synthesize porous MN as well. For example, vanadium, molybdenum, tungsten, and titanium nitrides with a reasonable high surface area can be synthesized from their respective chloride salts by activation with zinc chloride [ 180 ]. A mixture of individual metal chlorides, lithium nitride (Li 3 N), and zinc chloride in both hydrated and anhydrous forms was grounded into a solid mass and subjected to heating at a relatively low temperature of 290°C to obtain porous MNs ( Figure 8b ).…”
Section: Synthesis Of Porous Mnsmentioning
confidence: 99%
“…With the advantages of excellent conductivity, high hardness, and superior stability, transition-metal nitrides (TMNs) are widely applied in catalysis, energy storage, and medicine [42][43][44][45]. In recent years, TMNs have also been reported to be the SERS substrates [46][47][48][49][50]. For instance, Guan et al reported that ultrathin δ-MoN nanosheets were synthesized via a solution route at 270 o C and 12 atm, and the Raman EF of these nanosheets is determined to 8.16 × 10 6 [46].…”
Section: Introductionmentioning
confidence: 99%
“…George et al demonstrated that few-layered Ti2N MXenes exhibited ultrasensitive detection of explosives at micromolar level [47]. Xi et al developed a molten-salt method for preparing plasmonic vanadium nitride porous materials, which could be used as sensitive and stable SERS substrates [48]. Nevertheless, to the best of our knowledge, the current study is almost limited to titanium nitride, molybdenum nitride and vanadium nitride, the systematic preparation and research of other TMNs have not been reported, besides the Raman enhancement mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%